Pengembangan Strategi Digital Marketing pada UMKM Mie Bagan Siapi-Api Kota Batam - Lady, Lady; Jessy, Jessy (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2024)
Currently (MSMEs) in the culinary sector are developing rapidly in Batam City. The right and effective marketing for MSMEs in the culinary sector currently is to use digital marketing methods. The aim of this practical work is to develop a digital marketing strategy for Mie Bagan Siapi-Api MSMEs. The methods used in this practical work are interviews and observation. The results of implementing strategies from making photo designs on Instagram and Facebook feeds, location points for Nagoya FoodCourt and Mitra2 branches on Google Maps, creating logos, and Canva training for MSME owners show that consumers are starting to be interested in Mie Bagan Siapi-Api MSMEs which can be seen from the existence of The positive influence given to MSMEs, such as increasing the number of followers on the MSME Instagram account, changing the feed on Instagram to be neater, positive reviews on Google Maps and the presence of Linktree in the Instagram bio .This is one of the studies that carries out digital marketing strategies for MSMEs in Batam City.